Weightlifting movement assessment & optimization: Mobility & stability for the snatch and clean & jerk. A complete guide for athletes & coaches - Henoch, Q. (Catalyst Athletics, 2017)
A book about mobility and stability specifically for Olympic weightlifting by a qualified professional experienced in the sport. Henoch lays the ground work with clearly explained theory, and then provides a systematic process for recognizing problems, discovering their sources, and addressing them effectively, all with the express purpose of achieving safe, optimal positions and movement patterns for the snatch and clean & jerk. Contains over 900 photos and illustrations. Contents: Part I: Setting The Foundation Chapter 1: Terms, Concepts & Discussion Chapter 2: Trunk Stability & Weightlifting Posture Part II: Screening & Assessment Chapter 3: Screening & Assessment: The Pull & Split Chapter 4: Screening & Assessment: Transition & Overhead Chapter 5: Screening & Assessment: The Squat Part III: Building The Weightlifting Movements Chapter 6: Programming Considerations The Snatch Chapter 7: Snatch Starting Position Chapter 8: Snatch First Pull Chapter 9: Snatch Finish/Extension Chapter 10: Snatch Third Pull Chapter 11: Snatch Receiving Position Chapter 12: Summary of The Snatch The Clean Chapter 13: Clean Receiving Position Chapter 14: Summary of The Clean The Jerk Chapter 15: Jerk Front Rack Chapter 16: Jerk Dip Chapter 17: Jerk Drive Chapter 18: Jerk Split Chapter 19: Summary of The Jerk Chapter 20: Variations for Skill Transfer Chapter 21: Recovery